Peran Healing dalam Mengurangi Tekanan Akademik: Perspektif Mahasiswa Baru Fakultas Hukum Universitas Sultan Ageng Tirtayasa - Fazia Caesarizka Sungkar; Hawari Raissa Baihaqi; Saskia Nopa Lestari; Talitha Dewani (Yayasan Al-Afif, 2025)
Facing academic pressure in the early stages of college, first-year students at the Faculty of Law, Sultan Ageng Tirtayasa University, often feel overwhelmed by the high academic demands. Social support, such as talking with friends or spending time with family, plays a significant role in alleviating the academic stress they experience. While these healing techniques provide temporary relief, students still feel stressed, especially when assignments pile up or exams approach. This study found that while healing through social support helps reduce anxiety in the short term, students also need more structured and sustainable coping skills, such as time management and more effective stress management strategies, to better handle the ongoing academic pressure.